1999
DOI: 10.1007/s002130050861
|View full text |Cite
|
Sign up to set email alerts
|

Actions of the D 1 agonists A-77636 and A-86929 on locomotion and dyskinesia in MPTP-treated L -dopa-primed common marmosets

Abstract: Common marmosets show parkinsonian motor deficits following 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) administration and develop dyskinesias during chronic L-dopa exposure. The D1 agonists A-77636 [(1R, 3S) 3-(1'-adamantyl)-1-aminomethyl-3, 4-dihydro-5, 6-dihydroxy-1H-2-benzopyran HCl] and A-86929 [(-)-trans 9, 10-hydroxy-2-propyl-4, 5, 5a, 6, 7, 11b-hexahydro-3-thia-5-azacyclopent-1-ena[c]phenanthrene hydrochloride] possess potent antiparkinsonian activity in the MPTP-treated marmoset and we now ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 38 publications
(76 reference statements)
4
24
0
Order By: Relevance
“…Our present findings confirm that D1/D5 agonists can induce AIMs in parkinsonian rodents (Monville et al, 2005). Studies performed in MPTP-lesioned monkeys are to some extent contradictory on this matter, yet most emphasize that D1/D5 agonists induce significant dyskinesia (Blanchet et al, 1996;Pearce et al, 1999;Goulet and Madras, 2000) and the D1/D5 agonist ABT-431 is as potent as levodopa in inducing dyskinesia in patients (Rascol et al, 2001). Remarkably, we found that SKF-81297 induced significantly more MD than apomorphine and quinpirole, what is consistent with reports showing that D1/D5 agonists increase oral movements in rats and monkeys with intact dopaminergic pathways (Bedard and Boucher, 1989;Waddington et al, 1995) and produce abnormal dyskinetic oral movements in MPTP-lesioned marmosets (Gnanalingham et al, 1995).…”
Section: D1/d5 Dopamine Receptor Agonists Are More Powerful Inductorssupporting
confidence: 81%
See 1 more Smart Citation
“…Our present findings confirm that D1/D5 agonists can induce AIMs in parkinsonian rodents (Monville et al, 2005). Studies performed in MPTP-lesioned monkeys are to some extent contradictory on this matter, yet most emphasize that D1/D5 agonists induce significant dyskinesia (Blanchet et al, 1996;Pearce et al, 1999;Goulet and Madras, 2000) and the D1/D5 agonist ABT-431 is as potent as levodopa in inducing dyskinesia in patients (Rascol et al, 2001). Remarkably, we found that SKF-81297 induced significantly more MD than apomorphine and quinpirole, what is consistent with reports showing that D1/D5 agonists increase oral movements in rats and monkeys with intact dopaminergic pathways (Bedard and Boucher, 1989;Waddington et al, 1995) and produce abnormal dyskinetic oral movements in MPTP-lesioned marmosets (Gnanalingham et al, 1995).…”
Section: D1/d5 Dopamine Receptor Agonists Are More Powerful Inductorssupporting
confidence: 81%
“…But the neural mechanisms of dopamine agonist-induced dyskinesia are thought to essentially concern the indirect pathway (Crossman, 1990;Obeso et al, 2000) and our findings suggest a primary involvement of the D1 receptor regulated direct pathway. A primary involvement of D1 receptors and the direct basal ganglia pathway is suggested by other recent studies too (Aubert et al, 2005;Fiorentini et al, 2006), and by the fact that D2 family agonists are less likely to induce dyskinesia in patients and animal models of PD than unselective and D1/D5 selective agonists (present findings; Gnanalingham et al, 1995;Blanchet et al, 1996;Pearce et al, 1999;Goulet and Madras, 2000;Nutt, 2000;Rascol et al, 2001;Lundblad et al, 2002;Monville et al, 2005). A recent study established that levodopa-induced dyskinesia in the rat 6-OHDA model is related to increased synchronization of afferent activity to the basal ganglia output nuclei (Meissner et al, 2006).…”
Section: Severity Of Fd Is Related To Striatal and Motor Cortex Bold supporting
confidence: 71%
“…However, in contrast to the studies cited above, chronic administration of the selective and long-acting D 1 agonist A-77,636 led to a gradual reduction in dyskinesia severity, in the primed MPTP-lesioned common marmoset (Pearce et al, 1999). Although that last study was not a de novo study, it highlights the importance of pulsatile dopamine receptor stimulation in the pathophysiology of LID.…”
Section: B Pulsatile Dopaminergic Therapymentioning
confidence: 72%
“…Short-acting D1 and D2 receptor ago-nists have both been shown to induce dyskinesia in animal models of parkinsonism. 303 However, in MPTP monkeys the pure D1 agonists A-86929 and A-77636 provide motor benefits with reduced dyskinesia, 1032,1033 and there is renewed interest in studying these agents in patients with PD. Recent studies have implicated the D3 receptor in the induction of dyskinesia, 305 and the partial D3 agonist BP897 ([N-[4-(4-(2-methoxyphenyl)piperazinyl)butyl]-2-naphthamide) has been shown to provide antiparkinsonian effects and reversal of dyskinesia in both macaque and squirrel monkeys.…”
Section: Treatment Of Dyskinesias and Motor Fluctuationsmentioning
confidence: 99%